Directs effects of granulocyte-macrophage colony stimulating factor (GM-CSF) on adaptive immunogenesis - Victor Ivanovich Seledtsov; Vladimir V. Malashchenko; Natalja D. Gazatova; Maksim E. Meniailo; Ekaterina M. Morozova; Galina V. Seledtsova (Taylor & Francis Group, 2019)
Background: We studied direct effects of human granulocyte-macrophage colony stimulating factor (GM-CSF) on phenotypical characteristics and cytokine-production of non-activated and activated human monocytes/macrophages (Mc/Mphs) and T cells. Methods: Purified Mc/Mphs were activated by bacterial lipopolysaccharide (LPS, 1 μg/ml) for 24 h, while T cells were activated by particles conjugated and antibodies (Abs) against human CD2, CD3, and CD28 for 48 h. Results: GM-CSF treatment (0.01-10 ng/ml) was shown to reduce percentages of CD197 (CCR7)-positive cells in non-activated Mph cultures, without affecting significantly CD14+ (LPS co-receptor), CD16+ (FcγRIII, low-affinity Fc-receptor), CD119+ (interferon-gamma receptor 1), and CD124+ (IL4 receptor α-subunit) cells. In addition, GM-CSF reduced relative numbers of CD197+ cells, as well as CD14+, CD16+, and CD119+ cells in activated Mph cultures without affecting CD124+ cell distribution. GM-CSF at the highest dose of 10 ng/ml enhanced TNF-α and IL-6 (but not IL-1β and IL-10) production in activated Mc/Mphs. In activated T cell cultures, GM-CSF at 0.1-1.0 ng/ml augmented CD38+ cell numbers in naïve СD45RA+/СD197+ and central memory СD45RA−/СD197+ cell subsets, with no effect on effector СD45RA−/СD197− and terminally differentiated effector СD45RA+/СD197− cells. GM-CSF at a low dose (0.01 ng/ml) down-regulated INF-γ production, while at a high dosage (10.0 ng/ml) up-regulated IL-2 and IL-4 production. Conclusion: In general, the results suggest that GM-CSF is able to facilitate the implication of both Mph and T cells in the adaptive immunogenesis.